Faktor Risiko Obesitas pada Siswa MAN 1 Banda Aceh - Irma Suryani; Maidar Maidar; Fahmi Ichwansyah Fahmi Ichwansyah; Hermansyah Hermansyah; Asnawi Abdullah (FORIKES, 2023)
The prevalence of excess nutrition in adolescents continues to increase, which can increase the risk of non-infectious diseases such as diabetes, hypertension, heart problems and psychological problems. In Aceh, cases of overweight and obesity in teenagers reached 11.6%, and this is thought to be caused by a diet dominated by instant processed foods, soft drinks, fast food, and lack of physical activity. This study aimed to analyze the relationship between fast food consumption habits, snacking habits, duration of watching television and playing games, physical activity, nutritional knowledge, pocket money, and place of residence and obesity in MAN 1 Banda Aceh students. This study used a cross-sectional approach. Data was collected through filling out questionnaires and measuring weight and height. Data were analyzed using the logistic regression test. Based on the test results, it was found that the p value for each factor was frequent consumption of fast food = 0.163, frequent snacking = 0.056, duration of watching & playing games = 0.061, nutritional knowledge = 0.852, pocket money = 0.901, residence in a dormitory = 0.025, residence in boarding house = 0.005 and lack of physical activity = 0.604. It was concluded that the risk factors for obesity in MAN 1 Banda Aceh students were residence in a dormitory = 0.025 and residence in a boarding house = 0.005Keywords: obesity; teenager; residence ABSTRAK Prevalensi kelebihan gizi pada remaja terus meningkat, yang dapat meningkatkan risiko penyakit non-infeksi seperti diabetes, hipertensi, gangguan jantung, serta masalah psikologis. Di Aceh, kasus kegemukan dan obesitas pada remaja mencapai 11,6%, dan hal ini diduga disebabkan oleh pola makan yang didominasi oleh makanan olahan instan, minuman ringan, makanan cepat saji, dan kurangnya aktivitas fisik. Studi ini bertujuan untuk menganalisis hubungan antara kebiasaan konsumsi makanan cepat saji, kebiasaan mengemil, durasi menonton televisi dan bermain game, aktivitas fisik, pengetahuan gizi, uang saku, dan tempat tinggal dengan obesitas pada siswa MAN 1 Banda Aceh. Studi ini menggunakan pendekatan cross-sectional. Data dikumpulkan melalui pengisian kuesioner dan pengukuran berat dan tinggi badan. Data dianalisis menggunakan uji regresi logistik. Berdasarkan hasil uji ditemukan bahwa nilai p untuk setiap faktor adalah sering mengkonsumsi fast food = 0,163, sering ngemil = 0,056, durasi menonton & main game = 0,061, pengetahuan gizi = 0,852, uang jajan = 0,901, tempat tinggal di asrama = 0,025, tempat tinggal di kost = 0,005 dan aktivitas fisik kurang = 0,604. Disimpulkan bahwa faktor risio obesitas pada siswa MAN 1 Banda Aceh adalah tempat tinggal di asrama = 0,025 dan tempat tinggal di kost = 0,005Kata kunci: obesitas; remaja; tempat tinggal